Antara Terbuka, Tertutup, dan Campuran: Mencari Format Sistem Proporsional dalam Pemilihan Umum Legislatif di Indonesia - Hannan, Abd; Syarif, Zainuddin (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2023)
This study focuses on discussing the debate around the ideal format of the general election system in Indonesia, between open, closed, and mixed proportional systems. There are three research questions raised in this study, how is the application of a proportional system in the dynamics of elections in Indonesia? What are the weaknesses and strengths of implementing a proportional electoral system in Indonesia, both with open and closed systems? Is it possible for two electoral proportional systems (open and closed) to be mated into a new system, a mixed proportional system, for example? This research was conducted based on a qualitative approach. The sources and types of data used are secondary data, especially those from library materials such as books, journals, previous research results, and information media, both print and online. After analyzing field data based on the perspective of political sociology theory, this study found the finding that since it was first held in 1955, elections in Indonesia have used a proportional system to date, starting from a closed system and then moving on to an open system. At the practical level, both of these approaches have weaknesses. Closed proportionality tends to weaken people's participation, while open proportionality makes political parties not optimally carry out their party functions. In order to bridge this problem, a new approach is needed, one of which is to implement a mixed member proportional (MMP) system. In general, the idea of a mixed proportional system has advantages in terms of strengthening the function of political parties and the participation of the people to directly elect their representatives.